Quantification and potential functional relevance of binding cooperativity of adjacent transcription factors on DNA - Xinyao Wang; Chen Xie; Ke Shen; Dubai Li; Xiaoliang Sunney Xie (Proceedings of the National Academy of Sciences, 2025)
In eukaryotes, the expression of specific genes is regulated by a combination of transcription factors (TFs) bound on regulatory regions of the genomic DNA (promoters and enhancers). Recent advances in genomic sequencing technology have enabled the measurements of TFs’ footprints and binding affinities on DNA at the single-molecule level, facilitating the probing of binding cooperativity among adjacent TFs. This necessitates quantitative descriptions of TFs’ binding cooperativity and understanding of its potential functional relevance. In this study, we show that the binding cooperativities between two adjacent TFs can be quantified by the γ coefficient, which can be experimentally determined. Under thermodynamic equilibrium, the binding affinities of two TFs can either increase together (positive cooperativity) or decrease together (negative cooperativity), but not in opposing directions (one increases while the other decreases). Within the framework of thermodynamics, we investigate the functional relevance of cooperativity. The functional relevance of positive cooperativity, which has been extensively discussed in the literature, is the sigmoidal binding curve around a TF concentration threshold (analogous to oxygen binding to hemoglobin), whereas the functional relevance of negative cooperativity is twofold. First, mutual exclusion of the two TFs enables bidirectional gene switching, akin to the CI-Cro system in phage λ . Second, while TFs often exhibit intranuclear concentration fluctuations, negative binding cooperativity assures fast TF dissociation from DNA and hence rapid response for gene expression regulation. Furthermore, the nonequilibrium steady states of living cells can lead to either positive or negative cooperativity, which can also be quantified by the γ coefficient.